A Saree For Ammi - Mamta Nainy (Bharat Tulika Publishers, 2019)
Ammi weaves the most beautiful sarees, but never gets to wear any of them! Her two little daughters decide to do something about it - break their piggy bank! But is there enough in it to buy Ammi her very own saree? This gentle story goes into the home of a weaver's family, and lets warmth and affection add colour to their lives. Engaging visual details in vivid shades complement the simple, elegant text for a touch and feel experience of a village in Kota, Rajasthan, its sarees and its people.
Keywords: EY - RM -- EY - RM